Reducing Campylobacter jejuni Colonization of Poultry via Vaccination - Neal-McKinney, Jason M. (PLoS One, 2014)
Campylobacter jejuni is a leading bacterial cause of human gastrointestinal disease worldwide. While C. jejuni is a commensal organism in chickens, case-studies have demonstrated a link between infection with C. jejuni and the consumption of foods that have been cross-contaminated with raw or undercooked poultry. We hypothesized that vaccination of chickens with C. jejuni surface-exposed colonization proteins (SECPs) would reduce the ability of C. jejuni to colonize chickens, thereby reducing the contamination of poultry products at the retail level and potentially providing a safer food product for consumers. To test our hypothesis, we injected chickens with recombinant C. jejuni peptides from CadF, FlaA, FlpA, CmeC, and a CadF-FlaA-FlpA fusion protein. Seven days following challenge, chickens were necropsied and cecal contents were serially diluted and plated to determine the number of C. jejuni per gram of material. The sera from the chickens were also analyzed to determine the concentration and specificity of antibodies reactive against the C. jejuni SECPs. Vaccination of chickens with the CadF, FlaA, and FlpA peptides resulted in a reduction in the number of C. jejuni in the ceca compared to the non-vaccinated C. jejuni-challenged group. The greatest reduction in C. jejuni colonization was observed in chickens injected with the FlaA, FlpA, or CadF-FlaA-FlpA fusion proteins. Vaccination of chickens with different SECPs resulted in the production of C. jejuni-specific IgY antibodies. In summary, we show that the vaccination of poultry with individual C. jejuni SECPs or a combination of SECPs provides protection of chickens from C. jejuni colonization.